Possible beneficial effects of amlodipine, lisinopril, and their Combination on lipid profile in hypertensive patients - Alhamdani, Fadia Y. (The Iraqi Journal of Veterinary Medicine, 2009)
It is well known that monotherapy does not provide therapeutic response in all hypertensive. Somepatients show an excellent response, while in others there is a poor response. Combinationantihypertensive therapy is administered when blood pressure is inadequately controlled bymonotherapy to achieve a balanced and additive antihypertensive effect with minimum adverse effects.Both angiotensin converting enzyme (ACE) inhibitors and dihydropyridine type of calcium antagonistsare well established and widely used in monotherapy. An understanding of differences in themechanism of action of these agents allows a logical approach for the use of these agents as acombination therapy. This study was designed to evaluate the possible beneficial effects of long actingcalcium channel blocker, amlodipine and the long acting Angiotensin converting enzyme (ACE)inhibitor, lisinopril given either alone or in combination in patients with essential hypertension on lipidprofile (LDL-C and HDL-C) and on other parameters using a randomized double blind, crossoverstudy. The study includes 150 patients with systolic blood pressure (SBP)>140 mmHg and diastolicblood pressure (DBP) >90 mmHg received amlodipine 5 mg, lisinopril 5 mg and their combinationprior randomization schedule. Systolic, diastolic blood pressure and pulse rate were recorded at weeklyintervals while, serum levels of urea, creatinine, LDL-C and HDL-C where recorded at monthlyintervals, the duration of this study was 3 months. Results were obtained using paired students t-test,differences were considered significant with (p<0.05).A significant decline in SBP and DBP in all treatment groups (p<0.05) was recorded, the reductiontend to be more pronounced in the combination group. Moreover, there was a significant effect ofcombination on the heart rate, serum level of urea and creatinine, beside that, the level of HDL wassignificantly elevated with amlodipine and combination. We concluded that combination had additionalblood pressure lowering effect when compared either with amlodipine or lisinopril alone, in addition tothe greater effect on lipid profile which demonstrated that this combination is potentialantiatherosclerotic agent.